Evaluasi Kepatuhan Industri Konveksi UD. X di Kota Surabaya Terkait Perizinan Lingkungan - Redatu Putri, Yolanda Aprian; Cahyonugroho, Okik Hendriyanto (Faculty of Engineering, Universitas Serambi Mekkah, 2025)
This study aims to evaluate the compliance level of one of the convection industries in Surabaya City, UD. X towards environmental licensing. The methods used include empirical and qualitative juridical approaches. Data collection was carried out through the E-simpel website and direct supervision by PPLH. The results showed that UD. X has fulfilled administrative obligations and environmental documents but there are still discrepancies in the implementation of UKL-UPL with the applicable technical guidelines. Supervision and guidance of business actors need to be strengthened to ensure compliance with environmental licensing provisions. The provision of administrative sanctions to business actors can also be a solution to improve the compliance of business actors in the implementation of the UKL-UPL that has been owned.